Monitoring of CO2 emissions from vans, 2023 - Provisional data ... - European Environment Agency (European Environment Agency, 2024)
The Regulation (EU) No 2019/631 (and before that Regulation (EU) No 510/2011) requires Member States to record information for each new van registered in its territory. Every year, each Member State shall submit to the Commission all the information related to their new registrations. In particular, the following details are required for each new van registered: manufacturer name, type approval number, type, variant, version, make and commercial name, specific emissions of CO2, mass of the vehicle, wheel base, track width, fuel type and fuel mode. Additional information, such as engine power and engine capacity were also submitted. Data for EU-28 are reported in the main database. Since 2018 Iceland and since 2019 Norway are also included in the database. ...